Strategi Digital Marketing bagi Pelaku UMKM di Kota Sorong - Wardani, Elsya Aulia; Jamil, Ahmad; Wijiastuti, Retno Dewi; Zain, Evi Mufrihah; Andjar, Febry Jein; Arfandi, Arfandi; Prihandoko, Nurgroho Dwi (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role as a key pillar in strengthening the national economy, including in Sorong City, Southwest Papua Province. However, most MSME actors in this region still face limitations in utilizing digital technology as a marketing tool. In fact, advances in information technology and the high rate of internet penetration in Indonesia offer great opportunities for MSMEs to expand their market networks and enhance business competitiveness. This community service activity aims to improve the knowledge, skills, and awareness of MSME actors regarding the importance of digital-based marketing through a digital marketing socialization program. The implementation methods include material presentation, interactive discussions, and practical simulations using digital platforms. The results show a significant improvement in participants’ understanding of basic digital marketing concepts, their ability to create business accounts, independently upload products, and design simple promotional content using digital applications. In addition, participants demonstrated high enthusiasm throughout the activity and took the initiative to form a digital marketing learning community as a follow-up for continuous mentoring.